Unexpected pathogen presenting with purulent meningitis - Bering, Jamie (BMJ Case Rep, 2020)
Herein we report a case of a 67-year-old man with chronic lymphocytic leukaemia who developed acute onset of fever and altered mental status while receiving ibrutinib therapy. He was eventually found to have Capnocytophaga canimorsus meningitis. Timely diagnosis and appropriate antimicrobial therapy was associated with a favourable outcome. We describe challenges associated with appropriate identification of, and briefly review infections caused by Capnocytophaga sp. To our knowledge, this is the first case of invasive C. canimorsus infection in the setting of ibrutinib therapy, and adds to the growing list of serious infections that have been associated with this agent.